Enzymatic synthesis of hypermodified DNA polymers for sequence-specific display of four different hydrophobic groups - Ondruš, Marek; Sýkorová, Veronika; Bednárová, Lucie; Pohl, Radek; Hocek, Michal (Nucleic acids research, 2020)
A set of modified 2'-deoxyribonucleoside triphosphates (dNTPs) bearing a linear or branched alkane, indole or phenyl group linked through ethynyl or alkyl spacer were synthesized and used as substrates for polymerase synthesis of hypermodified DNA by primer extension (PEX). Using the alkyl-linked dNTPs, the polymerase synthesized up to 22-mer fully modified oligonucleotide (ON), whereas using the ethynyl-linked dNTPs, the enzyme was able to synthesize even long sequences of >100 modified nucleotides in a row. In PCR, the combinations of all four modified dNTPs showed only linear amplification. Asymmetric PCR or PEX with separation or digestion of the template strand can be used for synthesis of hypermodified single-stranded ONs, which are monodispersed polymers displaying four different substituents on DNA backbone in sequence-specific manner. The fully modified ONs hybridized with complementary strands and modified DNA duplexes were found to exist in B-type conformation (B- or C-DNA) according to CD spectral analysis. The modified DNA can be replicated with high fidelity to natural DNA through PCR and sequenced. Therefore, this approach has a promising potential in generation and selection of hypermodified aptamers and other functional polymers.
Keywords: dinukleosidfosfáty; cytosin; DNA-dependentní DNA-polymerasy; Polymerase Chain Reaction; DNA-Directed DNA Polymerase; párování bází; polymery; replikace DNA; Adenine; Uracil; deoxyribonukleosidy; Aptamers, Nucleotide; sekvence nukleotidů; Guanine; Deoxyribonucleosides; Polymers; uracil; hydrofobní a hydrofilní interakce; polymerázová řetězová reakce; Hydrophobic and Hydrophilic Interactions; adenin; DNA Replication; guanin; DNA; Base Pairing; aptamery nukleotidové; Dinucleoside Phosphates; Cytosine; Base Sequence